Treatment Modality and Quality Benchmarks of Aneurysmal Subarachnoid Hemorrhage at a Comprehensive Stroke Center - Yu, Wengui; Kavi, Tapan; Majic, Tamara; Alva, Kimberly; Moheet, Asma; Lyden, Patrick; Schievink, Wouter; Lekovic, Gregory; Alexander, Michael (Frontiers in Neurology, 2018)
Background: Aneurysmal subarachnoid hemorrhage (aSAH) is the most severe type of stroke. In 2012, the Joint Commission (TJC), in collaboration with the American Heart Association/American Stroke Association (AHA/ASA), launched the Advanced Certification for Comprehensive Stroke Centers (CSCs). This new level of certification was designed to promote higher standard of care for patients with complex stroke. Objective: The goal of this study was to examine the treatment modality and quality benchmarks of aSAH at one of the first five certified CSCs in the United States. Methods: Consecutive patients with aSAH at Cedars-Sinai Medical Center between April 1, 2012 and May 30, 2014 were included for this retrospective study. The ruptured aneurysm was treated with coiling or clipping within 24 hrs. All patients were managed per AHA guidelines. Discharge outcomes were assessed using modified Rankin Scale (mRS). The rate of aneurysm treatment, door-to-treatment time, rate of post-treatment rebleed, hospital length of stay (LOS), discharge outcome and mortality rates were evaluated as quality indicators. Results: The median age (interquartile range) of the 118 patients with aSAH was 55 (19). Among them, 84 (71.2%) were female, 94 (79.7%) were transfers from outside hospitals, and 74 (62.7%) had Hunt and Hess grade 1-3. Sixty patients (50.8%) were treated with coiling, 52 (44.1%) with clipping, and 6 (5.1%) untreated due to ictal cardiac arrest or severe co-morbidities. The rate of aneurysm treatment was 95% (112/118) with median door-to-treatment time at 12.5 (8.5) hours and 0.9% (1/112) post-treatment rebleed. The median ICU and hospital LOS were 12.5 (7) and 17.0 (14.5) days, respectively. Coiling was associated with significantly shorter LOS than clipping. There were 59 patients (50%) with favorable outcome and 19 deaths (16.1%) at hospital discharge. There was no significant difference in discharge outcome between coiling and clipping. Conclusions: Care of aSAH at one of the early CSCs in the United States was associated with high rate of aneurysm treatment, fast door-to-treatment time, low post-treatment rebleed, excellent outcome and low mortality rate. Coiling was associated with significant shorter LOS than clipping. There was no significant difference in discharge outcomes between treatment modalities.